Teriparatide as treatment of the Medication Related Osteonecrosis of the Jaws (MRONJ): a Scoping Review (Applied Sciences in Dentistry, 2025)
Introduction: Medication-related osteonecrosis of the jaw (MRONJ) is a serious complication affecting patients undergoing therapy with bisphosphonates and other antiresorptive agents. Teriparatide, a parathyroid hormone analog, has emerged as a possible therapeutic option to promote bone regeneration in these cases. This study aims to evaluate the efficacy of teriparatide in the treatment of MRONJ.Material and methods: An exploratory review was performed following Prisma ScR protocols using the following bibliographic databases Scopus, Pubmed, WOS, ScienceDirect to identify studies between the years 2020 and 2024 that have used teriparatide as a treatment to MRONJ.Results: From a total of 3100 articles, 8 were included in this review. The following were considered as relevant criteria: initial MRONJ status, dose and time of drug administration and possible adverse effects developed with this therapy. The studies reviewed reported a significant improvement in bone regeneration and a reduction in MRONJ symptoms in patients treated with teriparatide, highlighting the decrease in bone exposure and showing a favorable safety profile.Discussion: The findings suggest that teriparatide may be a viable and effective therapeutic option for the treatment of drug-associated osteonecrosis of the jaws. However, the need for further research, particularly long-term clinical trials, to confirm these results and optimize treatment protocols is highlighted.